2021
DOI: 10.3390/nu14010161
|View full text |Cite
|
Sign up to set email alerts
|

Food Security, Financial Resources, and Mental Health: Evidence during the COVID-19 Pandemic

Abstract: COVID-19 has negatively impacted many households’ financial well-being, food security, and mental health status. This paper investigates the role financial resources play in understanding the relationship between food security and mental health among U.S. households using data from a survey in June 2020. Results show job loss and savings draw down to pay for household bills had a significant relationship with both lower food security and greater numbers of poor mental health days during the pandemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…A study has found that higher education level affects food security after controlling for the household wealth index ( 36 ). Financial and economic crises have also been shown to have the highest impact on the food security status in developing countries ( 37 ), with economic status correlating directly with FI ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study has found that higher education level affects food security after controlling for the household wealth index ( 36 ). Financial and economic crises have also been shown to have the highest impact on the food security status in developing countries ( 37 ), with economic status correlating directly with FI ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Burden due to Restricted access to resources such as food, regular health care, or medication was related to an increased risk for probable PTSD. Earlier studies conducted in the USA reported associations between food insecurity and distress, as well as depressive and anxiety symptoms during the COVID-19 pandemic (Fang et al, 2021 ; Wolfson et al, 2021 ; Yenerall & Jensen, 2021 ).…”
Section: Discussionmentioning
confidence: 97%
“… 35 36 Empirical findings support the premise that household food insecurity or poverty increases with large households 14 and those living in rural or remote areas. 16 It is also empirically recognised that socioeconomic factors such as the receipt of remittances, 37 assistance, 38–40 access to finances, 19 21 41–43 income 14 16 and consumption level 23 play a significant role in explaining household food insecurity. Additional evidence in the literature suggests that demographic information about the family head, such as age, gender, marital status, employment and health status, are important elements that explain household food security.…”
Section: Methodsmentioning
confidence: 99%
“…Earlier studies obtained evidence of the socioeconomic and demographic factors that accounted for household food insecurity during the COVID-19 crisis. [14][15][16][17][18][19][20][21] To contribute to this growing knowledge, this study set out to answer the following research questions:…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%